2015
DOI: 10.17306/j.afs.2015.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of nectarine drying under near infrared – Vacuum conditions

Abstract: Nectarine (Prunus persica) is smooth-skinned peach of the rosaceae family, known for more than 2000 years and grown throughout the warmer temperate regions of both the northern and southern hemispheres.In tree shape and leaf characteristics the peach and nectarine are indistinguishable, but nectarine fruits look more like plums than peaches because of the smooth skin. The stones and kernels of the two fruits are alike in appearance. Nectarines have red, yellow or white fl esh and source of fi ber, iron, calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…The Ea values obtained when convective drying fall within the general range defined previously (Aral and Bese, 2016;Kaveh and Amiri Chayjan, 2017), which is 12.7 to 110 kJ/mol, determined for fruit and vegetables, and they are comparable to values reported in the literature, although the drying conditions are different. They are all particularly comparable to values in the range of 31.28 and 35.23 kJ/mol for the drying of nectarine slices at temperatures ranging from 50 to 70 °C (Alaei and Chayjan, 2015) and values of 31.94 and 34.49 kJ/mol for seeds of squash at temperatures of 50 and 80 °C, respectively (Chayjan et al, 2013), and those of melon sheaths varying between 27.6 and 45.3 kJ/mol (Golpour et al, 2016). These values are also similar to those (31.19 kJ/mol) obtained during the drying of tomato slices at 50-70 ⁰C (Azeez et al, 2017), mango ginger (32.6 kJ/mol) at 40-70 °C (Murthy and Manohar, 2014), unripe Cardaba banana (38.46 kJ/mol) at 50-70 °C (Olawoye et al, 2017), potato variety Golden delicious (35.3 kJ/mol) at 30-60 °C (Cruz et al, 2014) and pumpkin (33.74 kJ/mol) at 30-70 °C (Guiné et al, 2011).…”
Section: Activation Energysupporting
confidence: 70%
“…The Ea values obtained when convective drying fall within the general range defined previously (Aral and Bese, 2016;Kaveh and Amiri Chayjan, 2017), which is 12.7 to 110 kJ/mol, determined for fruit and vegetables, and they are comparable to values reported in the literature, although the drying conditions are different. They are all particularly comparable to values in the range of 31.28 and 35.23 kJ/mol for the drying of nectarine slices at temperatures ranging from 50 to 70 °C (Alaei and Chayjan, 2015) and values of 31.94 and 34.49 kJ/mol for seeds of squash at temperatures of 50 and 80 °C, respectively (Chayjan et al, 2013), and those of melon sheaths varying between 27.6 and 45.3 kJ/mol (Golpour et al, 2016). These values are also similar to those (31.19 kJ/mol) obtained during the drying of tomato slices at 50-70 ⁰C (Azeez et al, 2017), mango ginger (32.6 kJ/mol) at 40-70 °C (Murthy and Manohar, 2014), unripe Cardaba banana (38.46 kJ/mol) at 50-70 °C (Olawoye et al, 2017), potato variety Golden delicious (35.3 kJ/mol) at 30-60 °C (Cruz et al, 2014) and pumpkin (33.74 kJ/mol) at 30-70 °C (Guiné et al, 2011).…”
Section: Activation Energysupporting
confidence: 70%
“…model has also been suggested by others to describe the infrared drying of tomato by‐products (Celma et al . ) and nectarine (Alaei and Chayjan ).…”
Section: Resultsmentioning
confidence: 99%
“…This trend provides extra evidence for the suitability of the model to forecast the drying characteristics of apricot halves. The Midilli et al model has also been suggested by others to describe the infrared drying of tomato by-products (Celma et al 2008) and nectarine (Alaei and Chayjan 2015).…”
Section: Evaluation Of the Modelsmentioning
confidence: 99%
“…The values of ΔE, which expresses the total color change of orange slices after drying, varied between 6.33 and 14.72, and the effect of three drying methods on ΔE values was found to be statistically significant (p < 0.05). The ΔE values raised from 7.46 to 8.89, because of the increasing temperature of VID from 50 to 70 C. Alaei and Chayjan (2015) identified that the increase in the ΔE values of dried nectarine due to the increasing temperature of the VID from 50 to 70 C. The highest ΔE values of dried orange slices using different methods was detected in the TD groups, while the lowest content was detected in the VMD groups. In another study, the difference between ΔE values of strawberries dried using the VMD (5.76) and…”
Section: Quality Characteristics Of Dried Orange Slicesmentioning
confidence: 87%